2013
DOI: 10.1007/s13353-013-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

LXRα gene expression, genetic variation and association analysis between novel SNPs and growth traits in Chinese native cattle

Abstract: Liver X receptor α (LXRα) has emerged as an important regulator of lipid and energy metabolism. In this study, to better understand the effects of LXRα gene on growth traits in cattle, the mRNA tissue expression patterns and the polymorphisms of some exons of LXRα were revealed. The expression profile of the bovine LXRα gene was detected by quantitative real-time polymerase chain reaction (qRT-PCR) in 11 different Jiaxian cattle tissues and was found mainly expressed in spleen, liver, fat tissue, kidney, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…The ANGPTL4 rs4076317 polymorphism was associated with a higher percentage of body fat in adolescents as well as a higher waist-to-hip ratio in adults (Legry et al, 2009). In cattle, previous research into the expression profiles and SNPs of the bovine LXRα, ANGPTL4 and ANGPTL6 also indicated that these genes were mainly expressed in liver and adipose tissue and that they were significantly associated with growth and slaughter traits (height at withers, body length, hip width, height at hip cross and CW) of cattle (Mamedova et al, 2010;Li et al, 2012;Ma et al, 2014). Considering the similar functions of these new lipid and energy metabolism modulators, we hypothesized that ANGPTL3 may also be relevant to growth development of cattle.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ANGPTL4 rs4076317 polymorphism was associated with a higher percentage of body fat in adolescents as well as a higher waist-to-hip ratio in adults (Legry et al, 2009). In cattle, previous research into the expression profiles and SNPs of the bovine LXRα, ANGPTL4 and ANGPTL6 also indicated that these genes were mainly expressed in liver and adipose tissue and that they were significantly associated with growth and slaughter traits (height at withers, body length, hip width, height at hip cross and CW) of cattle (Mamedova et al, 2010;Li et al, 2012;Ma et al, 2014). Considering the similar functions of these new lipid and energy metabolism modulators, we hypothesized that ANGPTL3 may also be relevant to growth development of cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Animals in every breeding farm were under the same forage and feeding management conditions. The animals were weaned at an average of 6 months age and raised on a corn-corn silage diet, according to nutrient requirements of growing heifers (NRC, 2000;Ma et al, 2014). The NY animals were randomly chosen from the breeding center of Nanyang cattle (Nanyang city, Henan Province, P.R.…”
Section: Animals and Samplesmentioning
confidence: 99%
See 3 more Smart Citations